Performative Control and Rhetoric in Aotearoa New Zealand’s Response to COVID-19 - Gilray, Claire (Frontiers in Political Science, 2021)
This article analyses how specific nodal points of performative control developed and consequently structured the discourse on Aotearoa New Zealand’s response to the COVID-19 pandemic. It identifies these points by adopting a rhetorical-performative approach to uncover three particular performances of control that articulated the pandemic in Aotearoa New Zealand, from the diagnosis of the first COVID-19 case in the country in February 2020 through to October 2020. This period of analysis covers the emergence, subsequent nationwide lockdown, elimination, and re-emergence of the virus. There are three distinct nodal points that unfold as key to the nation’s ability to control COVID-19: the hegemonic “us”; iwi regionalism; and the rhetoric of kindness. A mixed approach of content analysis of government data, Facebook data, and key imagery is employed to constitute these nodal points’ relevance and how they structured the performative control that threaded through the nation’s initial response as a whole. The article demonstrates how Aotearoa New Zealand, considered by popular assessment to have been successful in its response to COVID-19, managed to eliminate the virus twice in 2020, but not without aspects of the antagonisms that have beset other nations. These include the exacerbation of internal dichotomies and questions about the legality of Government mandates. As the country’s response to COVID-19 is traced, the employment of a rhetorical-performative framework to identify the key nodal points also highlights how the framework could be applied to Aotearoa New Zealand’s continuing response as the pandemic endures.